Breast Pumps and Mastitis in Breastfeeding Women: Clarifying the Relationship - Mitoulas, Leon R.; Davanzo, Riccardo (Frontiers in Pediatrics, 2022)
Mastitis is a debilitating condition that can impact around 20% of mothers and is characterized by fever, flu-like symptoms and tender, swollen areas of the breasts. Despite the emerging evidence that breast milk dysbiosis is an underlying cause of mastitis, breast pumps have been implicated as a predisposing risk factor in the pathophysiology of mastitis in breastfeeding mothers. Previous studies have suggested that the use of a breast pump increases a mother's risk for developing mastitis, however, incidence rates of mastitis over the stages of lactation do not match breast pump usage rates. Furthermore, breast pumps, even when used at low vacuum, still promote some breast drainage, thus avoiding milk stasis, which is considered a key factor in the development of mastitis. As a consequence, these data suggest that the literature association of breast pumps with mastitis is more a case of reverse causation and not direct association. Moreover, it is important to note that breast pumps are actually a part of the conservative management of mastitis. In combination, these data show that the breast pump should not be considered a driver in the pathophysiology of mastitis in women.